SIFAT FISIK DAN KIMIA WOOD PELLET DARI LIMBAH INDUSTRI PERKAYUAN SEBAGAI SUMBER ENERGI ALTERNATIF - Arsad, Effendi (Kementerian Perindustrian, 2014)
Carakteristic physical and chemistry of Wood pellet from Industrial Disposal of Wood as Sources Energy Alternatif The research to gaved for physical and chemistry of Wood pellet from Industrial. Processing approximately 12%, sawdust dried to moisture content of sieved that is size of 15 mesh, 25 mesh and 35 mesh. Heating temperature were 60 0C and 110 0C. Moisture content of flawer wood pellet 4,46% - 9,95%, acacia wood pellet were 4.38% - 7.52% and tarap wood pellet were 4.60% - 9.98%. Density of flawer wood pellet were 0.51 - 0.78, acacia wood pellet were 0.61 - 0.78 and tarap wood pellet were 0.56 - 0.71, ash content of wood flawer from 0.87 - 2.04%, acacia 0.54 - 0.94% and ash content of tarap wood 1.71 - 2.05%. Calorific value of wood pellets flawers wood 3921,12 - 4150,19 cal/g, acacia wood 4022,29 - 4254,91 cal/g and tarap wood 3920,13 - 4125,28 cal/g. The higher temperature of the heating effect on reality the reduction of water and the weight of ash wood pellets while it was increasing calorific value.Keywords: waste wood, flawers wood, acacia wood, tarap wood, wood pellet